Neural dynamics of inflectional and derivational processing in spoken word comprehension: laterality and automaticity - Whiting, Caroline M.; Marslen-Wilson, William D.; Shtyrov, Yury (Frontiers in Human Neuroscience, 2013)
Rapid and automatic processing of grammatical complexity is argued to take place during speech comprehension, engaging a left-lateralised fronto-temporal language network. Here we address how neural activity in these regions is modulated by the grammatical properties of spoken words. We used combined magneto- and electroencephalography (MEG, EEG) to delineate the spatiotemporal patterns of activity that support the recognition of morphologically complex words in English with inflectional (-s) and derivational (-er) affixes (e.g. bakes, baker). The mismatch negativity (MMN), an index of linguistic memory traces elicited in a passive listening paradigm, was used to examine the neural dynamics elicited by morphologically complex words. Results revealed an initial peak 130-180 ms after the deviation point with a major source in left superior temporal cortex. The localisation of this early activation showed a sensitivity to two grammatical properties of the stimuli: 1) the presence of morphological complexity, with affixed words showing increased left-laterality compared to non-affixed words; and 2) the grammatical category, with affixed verbs showing greater left-lateralisation in inferior frontal gyrus compared to affixed nouns (bakes vs. beaks). This automatic brain response was additionally sensitive to semantic coherence (the meaning of the stem vs. the meaning of the whole form) in fronto-temporal regions. These results demonstrate that the spatiotemporal pattern of neural activity in spoken word processing is modulated by the presence of morphological structure, predominantly engaging the left-hemisphere’s fronto-temporal language network, and does not require focused attention on the linguistic input.